COMPARATIVE EVALUATION OF REPRODUCTIVE PERFORMANCE OF GRADED AND CROSSBRED CATTLE OF CHHATTISGARH IN FIELD CONDITION - KHUNTE, N; MUKHERJI, K; JAIN, V; PATEL, B (The Indian Journal of Animal Reproduction, 2017)
The present study was undertaken to assess the reproductive performance of crossbred (Holstein Friesian/ Jersey crossbred) and graded (Gir, Sahiwal and Red Sindhi grade) cattle (n=200) in Chhattisgarh. The age at first calving and dry period for crossbred cattle was lower (p<0.05) compared to other group of cattle. The period and season of calving as well as parity had no impact on reproductive parameters of crossbred or graded cattle. All the reproductive parameters improved (p<0.05) following availability of concentrate, green forage and dry fodder to animals compared to others receiving dry fodder or dry fodder and concentrate only. In brief, the crossbred cattle had superior reproductive performance over graded cattle, and the nutrition had influence on their reproductive performance.